The Importance of The Community Skill Building Program (CSBP) Toward The Trend of Early Marriage of Adolescent Girls in Tasikmalaya City - Rosuliana, Novi Enis; Nurhayati, Tetik; Aryanti, Dewi; Biswas, Happy Bandana (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: Early marriage occurs in many countries worldwide, especially in Indonesia, one of the ten countries with the highest number of child marriages under 18. Lack of knowledge about the impact of early marriage, poor socioeconomic level, culture, and family history of early marriage are influencing factors, so there is a need for an intensive program involving policymakers and empowering youth to reduce the incidence of early marriage. Therefore, the study aimed to determine the effect of the community skills building program (CSBP) on the tendency to early marriage in adolescent girls in Tasikmalaya.Methods: Research was quasi-experimental pre-post-test with a control group. The population is all adolescent girls in one of the public junior high schools in the city of Tasikmalaya, with a sample of 60 respondents who were selected using consecutive sampling. The inclusion criteria are adolescent girls aged 10-18 years, healthy and unmarried, for the exclusion criteria are adolescent girls who have moved domicile. Data retrieval using questionnaires on the tendency of early marriage contained 47 valid and reliable data. Data analysis used univariate and bivariate analysis with the Wilcoxon signed ranks test and Mann Whitney u test.Results: The results of data analysis showed that p-value 0.000 < p-value 0.05, which indicates a significant influence of the community skills building program (CSBP) on the tendency to early marriage in adolescent girls.Conclusions: It can be concluded that the application of the community skill-building program (CSBP) can reduce the tendency of early marriage in adolescent girls.